Failure pressure analysis of corroded pipeline with circumferential interacting defects subjected to combined loadings using FEM and ANN - A. Rahman, Ahmad Zairin Fadzil (IRC, 2021)
Among different fluid transportation methods such as in tanks, pipelines offer the most efficient means of transportation especially in an enormous amount of quantity.